2011
DOI: 10.1136/aim.2010.003889
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Rehabilitation and Acupuncture in the Treatment of a Professional Musician with Temporomandibular Joint Dysfunction

Abstract: This case study describes the use of acupuncture in a professional musician with myogenic temporomandibular dysfunction. The 3-year history of symptoms was associated with persistent episodic tension-type headaches. Acupuncture was used for trigger point release, primarily of the masticatory muscles, in conjunction with exercise therapy. After 8 weekly acupuncture sessions, the patient's pain had completely resloved, headaches had resolved and the Patient-Specifi c Functional Scale showed signifi cant improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Regarding the presence of a TMD on this single reed instrumentalist, there could be many options for the treatment. The different approaches for the treatment of a TMD are: cognitive behavioural therapy, acupuncture, physiotherapy, the use of an intra-oral appliances such as occlusal splints, pharmacologic treatment and in irreversible TMD pathologies surgical treatments [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the presence of a TMD on this single reed instrumentalist, there could be many options for the treatment. The different approaches for the treatment of a TMD are: cognitive behavioural therapy, acupuncture, physiotherapy, the use of an intra-oral appliances such as occlusal splints, pharmacologic treatment and in irreversible TMD pathologies surgical treatments [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on percussionists revealed the most severe pain in the cervical and lumbar spine, headaches, neuralgia within the upper extremities, exercise‐induced muscle tremor, and symptoms of depression caused by perceived dysfunctions (Macfarlance et al., ; Papandreou & Vervainioti, ). In addition to the overload of soft tissues in the upper extremities, violinists are often diagnosed with pain in the temporomandibular joint, head and neck, caused by the asymmetrical head position, holding, and pressure on the violin involving this joint (Bejjani, Kaye & Benham, ; Hunter, ).…”
Section: Discussionmentioning
confidence: 99%
“…When playing the violin, a musician takes a posture in which the head is leaning to the left side toward the violin, and the chin is directed to the right, causing the permanent contracture of the sternocleidomastoid muscle on the left side, and its stretching on the right side (Levy, Lee, Brandfonbrener, Press & Levy, ; Nagai & Eng, ). The left branch of the mandible and the left temporomandibular joint are involved in pressing down and holding the violin in position (Hunter, ; Kapandji, ); the left upper extremity is adducted and flexed in the shoulder joint, flexed in the elbow joint, the forearm and hand are in the supine position, the fingers of the left hand are flexed, the thumb is abducted and flexed to embrace and press the strings, the right free upper extremity is abducted to a 90° angle and flexed in the elbow joint to a 90° angle, the forearm and hand are pronated, and the fingers are positioned in a pinch grip to hold the violin bow (Berque & Gray, ; Sahrmann, ). In the sitting position, the left part of the shoulder girdle leans and rotates toward the right hip joint.…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapists (PTs) deal with TMJ as they treat other joints in the body and use different electrotherapy modalities such as electrical stimulation [16][17][18][19][20], ultrasound [21], acupuncture [22][23][24], and laser therapy [25][26][27] to reduce pain and inflammation which further promotes healing of tissues. Other conservative approaches including occlusal splint therapy [28], massage [28][29][30], manual therapy [4,31,32], therapeutic exercises, and home exercises program [33,34] are used to re-establish the proper flexibility and muscular length/ strength.…”
Section: Introductionmentioning
confidence: 99%